Pengaruh Kepuasan Kerja, Beban Kerja Dan Komitmen Organisasi Terhadap Turnover Intention Perawat RS. Bhayangkara TK. III Manado - sakul, Amelia (JURNAL RISET BISNIS DAN MANAJEMEN, 2018)
Higher nurse turnover rates will have a serious impact on hospitals in the future.Â  The results of this study are job satisfaction, workload and organizational commitment have a significant effect on simultaneous turnover intention. Job satisfaction has no significant effect on partial turnover intention. Workload has a positive and significant impact on partial turnover intention. Work commitment has a negative and significant effect on partial turnover intentionKeywords: Job Satisfaction, Workload, Organizational commitment, Turnover Intention